2022
DOI: 10.1186/s12870-022-03733-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of GATA family genes in wheat

Abstract: Background Transcription factors GATAs were a member of zinc finger protein, which could bind DNA regulatory regions to control expression of target genes, thus influencing plant growth and development either in normal condition or environmental stresses. Recently, GATA genes have been found and functionally characterized in a number of plant species. However, little information of GATA genes were annotated in wheat. Results In the current study, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 60 publications
4
29
0
Order By: Relevance
“…GATA TFs are ubiquitous in plants and are closely related to plant growth and development, quality, and yield. They regulate the germination and dormancy of plant seeds [ 12 ], the formation of organs and morphogenesis [ 13 ], the synthesis and accumulation of chlorophyll pigments [ 14 ], responses to environmental stress [ 15 ], and other biological processes. Phytochrome-interacting factors (PIF) can regulate the expression of GNC (GATA21)- and GNL (GATA22)-related transcription factors that regulate seed germination [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…GATA TFs are ubiquitous in plants and are closely related to plant growth and development, quality, and yield. They regulate the germination and dormancy of plant seeds [ 12 ], the formation of organs and morphogenesis [ 13 ], the synthesis and accumulation of chlorophyll pigments [ 14 ], responses to environmental stress [ 15 ], and other biological processes. Phytochrome-interacting factors (PIF) can regulate the expression of GNC (GATA21)- and GNL (GATA22)-related transcription factors that regulate seed germination [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genes belonging to the GATA-gene family are involved in the activation of a series of genes related to the regulation of the response to changes in the photoperiod and additionally regulate the accumulation of chlorophyll [22]. Nevertheless, the regulatory function of these genes is affected by environmental changes, thus their expression indirectly changes under abiotic stresses, as was reported in recent studies [78,79]. In the present study, the expression of the VvGATA26-like gene showed no remarkable change between the stressed plants and the control plants, and only a slight up-regulation was observed in the stressed self-rooted plants of the Dichali cultivar.…”
Section: Discussionmentioning
confidence: 95%
“…While the exon intron structure of the subgroups did not display consistent gene structure patterns (especially regarding the intron number), the number of exons (2) was highly consistent and conserved compared to the variable intron number (1-10). Different gene structure patterns have been associated with the diverse functional roles of GATA TFs, as observed in other plant species (Feng et al, 2022;Peng et al, 2021). Understanding the tissue-specific expression and functional roles of GATA TFs can provide insights into their regulatory mechanisms in potato and other plants.…”
Section: Discussionmentioning
confidence: 99%